Rancang Bangun Sistem Informasi Penjualan Baju Thriff Dalam Meningkatkan Mutu Palayanan dan Jumlah Transaksi - Lalu Kerta Wijaya; Harianto Harianto; Hamzan Ahmadi (Infotek: Jurnal Informatika dan Teknologi, 2023)
The development of information technology is growing very rapidly, so it has a very important role in various fields, one of which is in the business field, there are still many companies or businessmen who need information systems to support all activities ranging from marketing, data and information management. Queen thrift is a shop engaged in the fashion or clothing business located in Masbagek, Masbagek sub-district, East Lombok. So far, for promotional or marketing media carried out by Queen Thrift shop owners, namely using social media. With this, new innovations are urgently needed, and convenience in the promotion process, as well as online services in the form of information systems. so that these products can be seen by consumers quickly without having to come to the store.  With this, it is necessary to update the old system to the new system, namely by creating an online sales information system. With the hope to facilitate monitoring, storage, calculations and reports. In order to be able to provide the right information needed by customers and the store itself.